Determinan Kejadian Stunting Pada Balita: Peran Literasi Gizi Ibu, Pemberian Makan Responsif, Dan Kepatuhan Pemantauan Pertumbuhan - Nabilah Nurul Ilma; Hasri Yulianti; Nurlaelah Al-Tadom; Diyan Maria Kristin; Matje Meriaty Huru (Jurnal Medicare, 2025)
Stunting remains a major chronic nutritional problem with long-term consequences for physical growth, cognitive development, and overall quality of life. In 2024, the global prevalence of stunting reached 23.2%, while Indonesia reported 21.5%, East Nusa Tenggara (NTT) 37.9%, and Kupang District even higher at 39.5%. Household-level factors such as maternal nutrition literacy, responsive feeding practices, and adherence to growth monitoring play an essential role in stunting prevention. A preliminary assessment indicated that many mothers still demonstrated limited nutrition literacy, suboptimal responsive feeding practices, and irregular participation in growth monitoring services. This study aimed to determine the influence of maternal nutrition literacy, responsive feeding, and growth monitoring compliance on stunting among toddlers. A descriptive-analytic design with a cross-sectional approach was applied, and data were analyzed using logistic regression. The findings showed that maternal nutrition literacy (b = –1.61; SE = 0.73; p = 0.034), responsive feeding (b = –1.93; SE = 0.62; p = 0.019), and growth monitoring (b = –1.82; SE = 0.76; p = 0.017) were significantly associated with stunting. Thus, improving maternal nutrition literacy, promoting responsive feeding practices, and strengthening compliance with routine growth monitoring are crucial strategies for reducing stunting among young children.